2020
DOI: 10.1111/1440-1681.13238
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effects of oleoylethanolamide, a high‐affinity endogenous ligand of PPAR‐α, on the management and prevention of obesity

Abstract: Along with an increase in overweight and obesity among all age groups, the development of efficacious and safe anti‐obesity strategies for patients, as well as health systems, is critical. Oleoylethanolamide (OEA), a high‐affinity endogenous ligand of nuclear receptor peroxisome proliferator‐activated receptor alpha (PPAR‐α), plays important physiological and metabolic actions. OEA is derived from oleic acid, a monounsaturated fatty acid, which has beneficial effects on body composition and regional fat distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 75 publications
(253 reference statements)
1
37
0
Order By: Relevance
“…Degradation of the immediate precursor lyso-PAF is probably a result of its increased transformation to PAF ( 63 ). The decreased levels of the lipid-amide OEA are probably a compensatory mechanism in sepsis-related weight loss and disturbed energy balance, because OEA is a modulator in food consumption and weight management and actually leads to satiation or meal termination ( 64 ). Even the restoration of the reduced bile acid TDCA and the elevated amino acid DOPA seems to be a positive regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of the immediate precursor lyso-PAF is probably a result of its increased transformation to PAF ( 63 ). The decreased levels of the lipid-amide OEA are probably a compensatory mechanism in sepsis-related weight loss and disturbed energy balance, because OEA is a modulator in food consumption and weight management and actually leads to satiation or meal termination ( 64 ). Even the restoration of the reduced bile acid TDCA and the elevated amino acid DOPA seems to be a positive regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In this context OEA is considered an endocannabinoid-like lipid, which interacts with the peroxisome proliferator-activated receptor-alpha (PPAR-α) and intervenes during the anti-inflammatory processes [ 73 ].…”
Section: Immunonutrition: the Role Of Specific Nutrients And Microbiomentioning
confidence: 99%
“…In view of the fact that SARS-CoV-2 infection leads to increase the pro-inflammatory cytokines, including IL-6 and IL-1β in COVID-19 patients via binding to the TLRs, an important components of the innate immune system, it is assumed that OEA inhibits this pathway through its anti-inflammatory properties [ 75 ]. OEA binds with high affinity to PPAR-α receptors and increases the expression level of anti-inflammatory cytokine such as IL-10, then initiates a cascade of events, which can attenuate the inflammatory responses [ 73 ]. Furthermore, OEA attenuates the inflammatory responses modulating the expression of TLR-4, and interfering with the ERK1/2/AP-1/STAT3 signaling cascade [ 73 ].…”
Section: Immunonutrition: the Role Of Specific Nutrients And Microbiomentioning
confidence: 99%
“…Previous studies have indicated that the down-regulation of OEA levels arises in situation such as exposure to stress, which contributes to the increase in inflammatory markers and the NAE catabolism (15,16). In the current epidemiological studies on inflammatory-related diseases, OEA is considered an endocannabinoid-like lipid, which interacts with the peroxisome proliferator-activated receptor-α (PPAR-α) and mediates the anti-inflammatory processes (17). It is generally accepted that the endocannabinoid system (ECS) consists of the membrane cannabinoid receptors (cannabinoid receptor type 1 [CB1R] and type 2 [CB2R]), endogenous ligands (endcannabinoids), and enzymes responsible for the synthesis and degradation of ligands (18).…”
Section: Oleoylethanolamidementioning
confidence: 99%